Effect of dose on irradiation-induced loop density and Burgers vector in ion-irradiated ferritic/martensitic steel HT9. Issue 26 (12th September 2018) - Zheng, Ce; Maloy, Stuart; Kaoumi, Djamel
ABSTRACT: Samples of F/M steel HT9 were irradiated to 20 dpa at 420°C, 440°C and 470°C in a transmission electron microscope with 1 MeV Kr ions so that the microstructure evolution could be followed in situ and characterised as a function of dose. Dynamic observations of irradiation-induced defect formation and evolution were made at the different temperatures. Irradiation-induced loops were characterised in terms of their Burgers vector, size and density as a function of dose and similar observations and trends were found at the three temperatures: (i) botha /2 <111> anda <100> loops are observed; (ii) in the early stage of irradiation, the density of irradiation-induced loops increases with dose (0–4 dpa) and then decreases at higher doses (above 4 dpa), (iii) the dislocation line density shows an inverse trend to the loop density with increasing dose: in the early stages of irradiation, the pre-existing dislocation lines are lost by climb to the surfaces while at higher doses (above 4 dpa), the build-up of new dislocation networks is observed along with the loss of the radiation-induced dislocation loops to dislocation networks; (iv) at higher doses, the decrease of number of loops affects more thea /2 <111> loop population; the possible loss mechanisms of thea /2 <111> loops are discussed. Also, the ratio ofa <100> toa /2 <111> loops is found to be similar to cases of bulk irradiation of the same alloy using 5 MeV Fe 2+ ions to similar doses of 20 dpa at similar temperatures.